Comparison of Flavonoid Contents between Common and Tartary Buckwheat (Fagopyrum) Sprouts Cultured with/without Soil - Valan Arasu, Mariadhas; Kim, Sun-Ju; Abdullah Al-Dhabi, Naif; Suzuki, Tatsuro; Yamauchi, Hiroaki; Lee, Sang-Won (Asian Journal of Chemistry, 2014)
Buckwheat has been used as a traditional food and medicine in China, Japan and Korea. Phenolic compounds including chlorogenic acid, orientin, isoorientin, vitexin, isovitexin, rutin and quercetin were quantified with their commercial standards using high performance liquid chromatography (HPLC) in dry weight in 'Hokkai T10', 'Hokkai T8' and 'Kitawase' sprouts. The highest total phenolic content mean 48.76 mg g-1 dry weight was found in 'Hokkai T9' sprouts followed by mean 40.76, 38.09, 37.67 mg g-1 dry weight in 'Hokkai T10', 'Hokkai T8' and 'Kitawase' sprouts, respectively, with soilless practice at 10 DAS. The major metabolites found in common buckwheat sprouts were orientin, isoorientin, vitexin, isovitexin, rutin, but only rutin in Tartary buckwheat sprouts. In particular, rutin content in soilless-grown sprouts (mean 33.59 and 47.93 mg g-1 dry weight in 'Hokkai T 8' and 'Hokkai T 9', respectively) at 10 DAS was 20-40 % higher than that at 7 DAS.